Sensitivity of antifungal preparations of Сandida isolates from sub-biotopes of the human oral cavity - OsypchukN. О.; Nastenko, V. B.; Shirobokov, V. P.; Korotkyi, Y. V. (Regulatory Mechanisms in Biosystems, 2020)
Candidiasis is the commonest opportunistic infection of the oral cavity. As a result of immune-deficiency of the organism, yeasts of Candida genus by acting as commensal organisms transmute into pathogenic organisms. The article presents frequency of isolation, topographic peculiarities, species range, sensitivity of the Candida yeasts to antimycotics and newly-synthesized derivatives of amino alcohols isolated from the sub-biotopes of the oral cavity of patients with oncopathologies. The survey of the material included microscopic, mycologic, statistical-analytical methods. For all the clinical isolates the sensitivity to antifungal preparations was determined. Over the study 492 sub-biotopes of the oral cavity were examined. The extraction of the material was made from the mucous membrane of the cheek, angle of the mouth, mucous membrane of the surface of the tongue and the palate. According to the results of the conducted studies, the level of candidal carriage on the mucous membrane of the oral cavity in the patients with oncopathologies without clinical signs of candidiasis equaled 25.0%, active candidiasis infection was found in 47.0% of cases. Among the clinical strains, we isolated: C. albicans, C. glabrata, C. tropicalis and C. krusei. Among all the isolated strains, in all 4 sub-biotopes C. albicans dominated accounting for 73.1%. In 4 sub-biotopes we detected the association of two species of Candida. Analysis of the obtained results of the susceptibility of strains to modern antymicotics and newly-synthesized substances revealed that the representatives of non-albicans are more resistant to the antifungal preparations. Among the commercial preparations, amphotericin B exerted the highest activity against the clinical isolates of yeast-like fungi. The concentration of 0.97 µg/mL inhibited 50.0% of representatives of non-albicans, and also 75.0% of isolates of C. albicans. Fluconazole exhibited activity in the concentration of 1 µg/mL towards 17.0% of non-albicans and 25.0% of С. albicans. Itraconazole was observed to have no significant antifungal activity. Among the newly-synthesized aryl acyclic amino alcohols, compound Kc22 displayed high activity against both groups of Candida (experimental and control) making it promising for creating new therapeutic preparations. The parameters of resistance of clinical isolates to modern antimycotics indicate the necessity of constant monitoring of the sensitivity of the pathogens of candidiasis and precise species identification for rational use of antifungal preparations and prevention of the development of antimycotic resistance.